Halal Industry of 5.0 Era in Islamic Economic Scholar Perspective - Mu’is, Ahmad; Farida, Laila; Zuraidah (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
The halal industry is an inevitability of the development of a business where there is demand (demand), then there is someone who provides (supply). And the prospects are very promising with increasing growth from time to time. Even though it is labeled halal which is synonymous with religious symbols, it is not a barrier for consumers of all religions and nations to enjoy it. Because halal in its development is a symbol of guaranteeing cleanliness, safety and product quality for the entire production chain. Modern global society sees the substance as not a skin. The Halal industry is not just a business machine in general, which is materialistic in nature and profit-oriented, but there are messages or values ??of Islamic teachings originating from the Qur'an and Hadith that must be upheld. Therefore, in his journey must be in accordance with the provisions of the Shari'a. Islamic economists, such as Yusuf Qardhawi, Syed Nawab Heidar Naqvi, Adiwarman Karim and Mustaq Ahmad gave their opinions on the ideal Halal Industry. They said that the essence of Islamic economics at least has the character of monotheism (uluhiyyah-rububiyyah), humanity (insaaniyah), ethical norms (akhlaqiyyah), balance (wasathiyyah), free will (ikhtiyar) and responsibility (mas’uliyyah). If some of these become part of the business of Muslims, such as the halal industry, they will get material success (dhahir) and spiritual happiness (batin).